2017
DOI: 10.1038/s41598-017-18288-9
|View full text |Cite
|
Sign up to set email alerts
|

Thy-1 dependent uptake of mesenchymal stem cell-derived extracellular vesicles blocks myofibroblastic differentiation

Abstract: Bone marrow-derived mesenchymal stem cells (MSC) have been promoted for multiple therapeutic applications. Many beneficial effects of MSCs are paracrine, dependent on extracellular vesicles (EVs). Although MSC-derived EVs (mEVs) are beneficial for acute lung injury and pulmonary fibrosis, mechanisms of mEV uptake by lung fibroblasts and their effects on myofibroblastic differentiation have not been established. We demonstrate that mEVs, but not fibroblast EVs (fEVs), suppress TGFβ1-induced myofibroblastic diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 69 publications
2
65
0
Order By: Relevance
“…It is involved in cell–cell–matrix interaction, and it regulates fibrosis, promotes cell migration and adhesion . In the process of fibrosis, Thy‐1 can inhibit fibroblast trans‐differentiation and inhibit fibrosis by correlating with TGF‐β, which is called “fibrosis inhibitory gene”. It has been reported that DNA methylation occurs in Thy‐1 during idiopathic pulmonary fibrosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is involved in cell–cell–matrix interaction, and it regulates fibrosis, promotes cell migration and adhesion . In the process of fibrosis, Thy‐1 can inhibit fibroblast trans‐differentiation and inhibit fibrosis by correlating with TGF‐β, which is called “fibrosis inhibitory gene”. It has been reported that DNA methylation occurs in Thy‐1 during idiopathic pulmonary fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…54 In the process of fibrosis, Thy-1 can inhibit fibroblast trans-differentiation and inhibit FIGURE 4 Morphological, proliferative and fibrotic changes in RLE-6TN cells exposed to dust. Cells were exposed to 0, 25,50,100,150,200,300,400 fibrosis by correlating with TGF-β, 55 which is called "fibrosis inhibitory gene". It has been reported that DNA methylation occurs in Thy-1 during idiopathic pulmonary fibrosis.…”
Section: Dna Methylation Is An Epigenetic Modification Mediated Bymentioning
confidence: 99%
“…Several published studies have demonstrated that up-regulation of miR-486-5p and miR-630 contributes to IPF progression [45,46] and CADM1, OLFM4, PDGFRA as well as YAP1 genes play a crucial role in the pathogenesis of IPF [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…The amnion epithelium-derived EVs also had a direct effect on immune cells, including increased macrophage phagocytosis, reduced neutrophil myeloperoxidase, and suppressed T cell proliferation. Shentu and colleagues used human bone marrow MSC-derived EVs to suppress the transforming growth factor beta 1 (TGFβ1)-stimulated myofibroblast differentiation of normal and IPF lung fibroblasts [63]. They found that MSC-derived EVs utilized a Thy1-integrin dependent pathway for cell-to-cell communication for uptake into fibroblasts and the delivery of EV cargo and resulting anti-fibrotic activity.…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%